Peptide release after simulated infant in vitro digestion of dry heated cow’s milk protein and transport of potentially immunoreactive peptides across the caco-2 cell monolayer - Zenker, Hannah E.; Wichers, Harry J.; Tomassen, Monic M.M.; Boeren, Sjef; De Jong, Nicolette W.; Hettinga, Kasper A. (Nutrients, 2020)
Dry heating of cow’s milk protein, as applied in the production of “baked milk”, facilitates the resolution of cow’s milk allergy symptoms upon digestion. The heating and glycation-induced changes of the protein structure can affect both digestibility and immunoreactivity. The immunological consequences may be due to changes in the peptide profile of the digested dry heated milk protein. Therefore, cow’s milk protein powder was heated at low temperature (60 °C) and high temperature (130 °C) and applied to simulated infant in vitro digestion. Digestion-derived peptides after 10 min and 60 min in the intestinal phase were measured using LC-MS/MS. Moreover, digests after 10 min intestinal digestion were applied to a Caco-2 cell monolayer. T-cell epitopes were analysed using prediction software, while specific immunoglobin E (sIgE) binding epitopes were identified based on the existing literature. The largest number of sIgE binding epitopes was found in unheated samples, while T-cell epitopes were equally represented in all samples. Transport of glycated peptide indicated a preference for glucosyl lysine and lactosyl-lysine-modified peptides, while transport of peptides containing epitope structures was limited. This showed that the release of immunoreactive peptides can be affected by the applied heating conditions; however, availability of peptides containing epitopes might be limited.
Created from Fastlane, Scopus look-up
Keywords: Allergenicity; Caco-2 cell; Cow’s milk protein; Glycation; Immunogenicity; Peptides